A bipartite interaction with the processivity clamp potentiates Pol IV-mediated TLS - Seungwoo Chang; Luisa Laureti; Elizabeth S. Thrall; Marguerite S. Kay; Gaëlle Philippin; Slobodan Jergic; Vincent Pagès; Joseph J. Loparo (Proceedings of the National Academy of Sciences, 2025)
Processivity clamps mediate polymerase switching for translesion synthesis (TLS). All three Escherichia coli TLS polymerases interact with the β 2 processivity clamp through a conserved clamp-binding motif (CBM), which is indispensable for TLS. Notably, Pol IV also interacts weakly with the rim of the clamp through non-CBM residues. Ablating this “rim contact” in cells results in selective sensitivity to DNA-damaging agents, raising the question how the rim contact contributes to TLS. Here, we show that the rim contact is critical for TLS past a strong replication block but barely necessary for a weak blocking lesion. Within the in vitro reconstituted E. coli replisome, the rim mutation compromises Pol IV-mediated TLS past 3-deaza-methyl dA, a strong block, whereas barely affecting TLS past N 2 -furfuryl dG, a weak block. Similar observations are also made in E. coli cells bearing a single copy of these lesions in the genome. At lesion-stalled replication forks, single-stranded DNA binding protein locally enriches Pol IV, enabling it to bind the low-affinity rim site. This interaction poises Pol IV to better compete with Pol III, the replicative polymerase, which competitively inhibits Pol IV from interacting with the clamp through its CBM. We propose that this bipartite clamp interaction enables Pol IV to rapidly resolve lesion-stalled replication at a strong block through TLS, which reduces damage-induced mutagenesis.